Effect of Active Aspiration Drainage System Use on Postoperative Outcomes After Cardiac Surgery - Sofuoğlu, Mustafa Can; Ateş, Merve; Turhan, Emine; Hanedan, Muhammet Onur (The European Research Journal, 2026)
Objective: Postoperative drainage systems are essential for maintaining hemodynamic stability and enabling early detection of complications after cardiac surgery. This study aimed to evaluate the impact of an active suction drainage system applying negative pressure on postoperative morbidity and mortality. Methods: This single-center retrospective study included 153 patients who underwent open-heart surgery between August 2023 and August 2024. Patients were divided into two groups based on the drainage method: active suction drainage (n=69) and conventional drainage (n=84). Postoperative drainage volume, cardiac tamponade, re-exploration for bleeding, mortality, and postoperative complications such as acute kidney injury and wound infection were evaluated. Univariate logistic regression analyses were performed to assess potential confounding factors. Results: Cardiopulmonary bypass time, aortic cross-clamp time, and total operative duration were significantly longer in the active suction group (P=0.007, P=0.009 and P=0.010, respectively), while local hemostatic agent use was higher in the conventional group (P<0.001). Despite these differences, postoperative drainage volume, re-exploration rates, incidence of cardiac tamponade, acute kidney injury, wound infection, and mortality were comparable between groups (all P>0.05). Length of hospital stay was significantly longer in the active suction group. Univariate regression analyses did not identify any independent predictors of re-exploration or cardiac tamponade (P>0.05 for all variables). Conclusion: Active suction drainage was not associated with significant differences in major postoperative outcomes compared with conventional drainage methods. Although operative variables differed between groups, these factors did not demonstrate an independent effect on clinical outcomes. A numerically higher incidence of cardiac tamponade in the active suction group did not reach statistical significance and should be interpreted cautiously. Further large-scale prospective studies are warranted.